ENHANCING ESL NOVICE TEACHERS’ PROFESSIONAL DEVELOPMENT: ROLES OF PEERS IN OBSERVATIONAL LEARNING THROUGH PEER MENTORING - Hamdan, Norhaiza; Othman, Juliana; Lo, Yueh Yea (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
The transition from pre-service training to real-world classrooms can be daunting for novice English as a Second Language (ESL) teachers. A qualitative multiple-case study approach was employed to determine the impact of peer mentoring on ESL teachers’ professional development through mutual classroom observations. Specifically, peer mentors’ guidance on novice ESL teachers in developing effective instructions was appraised by applying Lortie’s (1975) apprenticeship of observation. The data were collected through interviews with three novice ESL teachers from public primary schools who participated in peer mentoring partnerships, classroom observations, and participants’ personal journal entries. Thematic analysis was performed, which demonstrated that peer mentoring facilitated a) enhanced instructional practices, b) a shift in the novices’ mindset and c) a collaborative interaction in the professional learning community. The findings posited that peer mentoring provided an alternative observational learning approach for novice ESL teachers in terms of effective instructional strategies from colleagues while obtaining specific feedback on professional development. Resultantly, a nuanced comprehension of the approach employed by novice ESL teachers to enhance instructional expertise via peer support was provided. Practical implications were contributed to existing ESL training programs, novice ESL teachers, and educational institutions.